PENERAPAN STAD PADA MATERI PERSAMAAN LINEAR SATU VARIABEL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP SUNAN GIRI MALANG - Vira Alfioni Babang Amah; Rio Febrianto Arifendi; Nila Kartika Sari (Universitas Tribhuwana Tunggadewi, 2024)
This study aims to examine the extent to which the Student Teams Achievement Division (STAD) cooperative learning model plays a role in improving mathematics learning outcomes on the topic of Single Variable Linear Equations (PLSV) for seventh-grade students at SMP Sunan Giri Malang. The research activities were carried out through the stages of planning, implementation, and evaluation of learning during the 2025 Professional Training Program (PLP). Data collection was conducted using initial tests (pretests), final tests (posttests), observation of student activities, and assessments of the learning process. The analysis results showed a very clear improvement, where the average student score increased from 24.50 to 79.83 after the implementation of STAD, and the mastery level of learning increased from 0% to 100%. These findings indicate that the implementation of STAD is effective in strengthening conceptual understanding, increasing student engagement, and fostering a more positive attitude towards mathematics.